Pengaruh Disiplin Kerja dan Budaya Organisasi terhadap Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Jombang - Mardi Astutik (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study was to examine the effect of labor discipline and organizational culture on employee performance in Legislative Council Secretariat of Jombang Regency. This study is a quantitative research using Likert scale as measurement method. The population used are all civil servants amounted to 37 respondents. Data collection technique used observation, questionnaires, interviews, and documentation. Variables of the research is work discipline and organizational culture on employee performance. Analysis of data using multiple regression analysis with the classical assumption. The results of the study indicate that the labor discipline (X1) has partial significant positive effect on employee performance which increasesalong with work discipline. Organizational culture (X2) has partial significant positive effect on employee performance. Performance of employees increases if supported with better organizational culture.